2015
DOI: 10.1104/pp.15.01379
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the light-specific metabolic and regulatory signatures of rice through combined in silico modeling and multi-omics analysis

Abstract: Light quality is an important signaling component upon which plants orchestrate various morphological processes, including seed germination and seedling photomorphogenesis. However, it is still unclear how plants, especially food crops, sense various light qualities and modulate their cellular growth and other developmental processes. Therefore, in this work, we initially profiled the transcripts of a model crop, rice (Oryza sativa), under four different light treatments (blue, green, red, and white) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 87 publications
4
70
0
Order By: Relevance
“…1). [4][5][6] The promoter analysis results also suggest the role of bZIP TF as a positive regulator, and bHLH TFs particularly PIFs as negative regulators of chlorophyll and carotenoid accumulation. 7 Among the bZIP TFs, HY5 is a strong antagonist of PIF and functions as an activator of genes for chlorophyll and carotenoid accumulation upon blue light signaling.…”
Section: Transcriptional Regulation Of Carotenoids Accumulationmentioning
confidence: 89%
See 1 more Smart Citation
“…1). [4][5][6] The promoter analysis results also suggest the role of bZIP TF as a positive regulator, and bHLH TFs particularly PIFs as negative regulators of chlorophyll and carotenoid accumulation. 7 Among the bZIP TFs, HY5 is a strong antagonist of PIF and functions as an activator of genes for chlorophyll and carotenoid accumulation upon blue light signaling.…”
Section: Transcriptional Regulation Of Carotenoids Accumulationmentioning
confidence: 89%
“…Although the biosynthesis of these compounds has been extensively studied, the information on the light-driven regulatory mechanism is relatively limited. In our recently published paper, 4 we have already discussed that in rice leaves, the highest and lowest accumulation of carotenoids and total phenolic in rice leaves, under blue light and dark conditions, respectively, following the order of blue>white>green>red>dark (carotenoids) and blue>whi-te>red>green>dark (total phenolics). We also found a very divergent gene expression pattern in leaves grown in blue and red lights, which was consistent with the observed phenotypes.…”
mentioning
confidence: 99%
“…To date, two rice GSMNs (Dharmawardhana et al, 2013; Liu et al, 2013) and three rice genome-scale metabolic models (GEMs) (Poolman et al, 2013; Seaver et al, 2014; Lakshmanan et al, 2015) have been reconstructed based on multiple data sources. Here, we make a distinction between GSMNs and GEMs, similar to the definitions used in Lewis et al (2012), where a GSMN comprises of all known metabolic reactions in an organism while a GEM is computable derivative of a metabolic network which can be analyzed using structural metabolic modeling and constraint-based modeling techniques such as FBA.…”
Section: Overview Of Current Rice Metabolic Network and Modelsmentioning
confidence: 99%
“…We tested the rice model from PlantSEED and found that the model has no stoichiometric inconsistency, but energy conservation is violated presumably due to the lack of manual curation in reaction reversibility. To the best of our knowledge, the most recent rice GEM is i OS2164 (Lakshmanan et al, 2015) reconstructed based on multiple databases including RiceCyc, PlantCyc, KEGG, and TransportDB (Ren et al, 2007). A distinct feature of this model is the detailed definition of all possible electron transport reactions in the mitochondrion, the plastid and the thylakoid including the light-driven photophosphorylation reactions in a wavelength specific manner, which allowed for the modeling of photosynthetic metabolism under different light sources.…”
Section: Overview Of Current Rice Metabolic Network and Modelsmentioning
confidence: 99%
See 1 more Smart Citation